Gut microbiota composition is associated with environmental landscape in honey bees. Issue 1 (30th November 2017) - Jones, Julia C; Fruciano, Carmelo; Hildebrand, Falk; Al Toufalilia, Hasan; Balfour, Nicholas J; Bork, Peer; Engel, Philipp; Ratnieks, Francis LW; Hughes, William OH
Abstract: There is growing recognition that the gut microbial community regulates a wide variety of important functions in its animal hosts, including host health. However, the complex interactions between gut microbes and environment are still unclear. Honey bees are ecologically and economically important pollinators that host a core gut microbial community that is thought to be constant across populations. Here, we examined whether the composition of the gut microbial community of honey bees is affected by the environmental landscape the bees are exposed to. We placed honey bee colonies reared under identical conditions in two main landscape types for 6 weeks: either oilseed rape farmland or agricultural farmland distant to fields of flowering oilseed rape. The gut bacterial communities of adult bees from the colonies were then characterized and compared based on amplicon sequencing of the 16S rRNA gene. While previous studies have delineated a characteristic core set of bacteria inhabiting the honey bee gut, our results suggest that the broad environment that bees are exposed to has some influence on the relative abundance of some members of that microbial community. This includes known dominant taxa thought to have functions in nutrition and health. Our results provide evidence for an influence of landscape exposure on honey bee microbial community and highlight the potential effect of exposure to different environmental parameters, such as forage type and neonicotinoid pesticides, on key honey bee gut bacteria. This work emphasizes the complexity of the relationship between the host, its gut bacteria, and the environment and identifies target microbial taxa for functional analyses. Abstract : We examine whether the composition of the gut microbial community of honey bees is affected by the environmental landscape the bees are exposed to. We find that the broad environment that forager bees are exposed to influences the relative abundance of members of the dominant microbial community, including taxa thought to have functions in nutrition and health.